Youth Awareness on Youth Development Law - Yeon, Asmah Laili; Azhar, Alias; Ayub, Zainal Amin; Abdullah, Siti Alida John; Arshad, Rozita; Suhaimi, Safiah (International Review of Management and Marketing, 2016)
Lack of awareness and understanding of youth development law amongst youth and policy makers is quite significant. Among the reasons that have been identified to be the root cause of this weakness is due to the failure or less priority given by the youth societies and related organization which are responsible in providing quality programmes for youth. In light of the above gap, the paper examines youth awareness on youth development law from the perspective of policy makers and youth themselves. This is a social-legal study, which involves two types of data collection; first, interviews with 53 policy makers/management from ministries, youth departments, youth agencies and societies; and result from a survey amongst Malaysian youth amounting to 4703. This study found that a majority of the respondents (the policy makers from ministries, state youth departments, youth societies and agencies) agreed that youth in Malaysia have a very low awareness or knowledge of the law relating to the youth. The lack of awareness also may be subjected from the absence of the legal awareness programme conducted by the related governmental agencies and organizations. However, the result of youth view is in contrast where the level of awareness of youth concerning policies of youth in law is quite high at the average of 77.8%. Nevertheless, the result shows more than 20% of youth in Malaysia do not aware about the existence of youth policy in law. Keywords: Youth Law, Youth Policy, Youth Awareness. JEL Classifications: K1, K12, K120